Acne Fulminans Induced by Lymecycline in a Patient with Hidradenitis Suppurativa: A Case Report - Ilaria Trave; Claudia Micalizzi; Mattia Molle; Riccardo Castelli; Emanuele Cozzani; Aurora Parodi (Karger Publishers, 2022)
Acne fulminans (AF) is a rare and severe form of inflammatory acne that typically occurs in male adolescents with acne vulgaris and is characterized by the sudden onset of painful, bleeding, and ulcerated lesions. It has been described very rarely in association with hidradenitis suppurativa (HS). Its onset may be induced by drugs, particularly isotretinoin. We present a case of a 16-year-old patient with HS who developed AF following initiation of antibiotic therapy with lymecycline. In the literature, only 2 patients who developed a coexistence of AF and HS have been reported, and there are only 2 other similar cases of AF induced by doxycycline and lymecycline. We consider our case to be of particular interest not only because of the very rare concomitant presence of AF and HS but also because AF was induced by lymecycline, a drug commonly used to treat both acne and HS, and described only once as a drug responsible for AF, so it is an aspect that deserves to be considered by the clinician dealing with similar conditions.